ANALISIS KESALAHAN UMUM BERBAHASA ASPEK EJAAN PADA KUMPULAN CERPEN KARYA SISWA MTS. AL-FIRDAUS - siti nurhasanah; Yeni Rostikawati (IKIP Siliwangi, 2023)
This study aims to classify and explain the spelling aspects of a collection of short stories by students of SMP IT Nurul Islah. The object of research, namely the analysis of spelling errors in a collection of short stories by students of SMP IT Nurul Islah. The method used in this research is descriptive analysis method. The analysis in this study is based on EYD. The error aspects analyzed include the use of conjunctions, errors in the use of capital letters, the use of absorption words, the use of prepositions. The number of errors in the short stories written by students was as follows: 20 in the use of conjunctions, 225 errors in the use of capital letters,13 in the use of pronouns word, 15in the use of absorption words, 93 in the use of prepositions.